GE_GERICHTE P/24092/2019 vom 9. Oktober 2025 - GE Cour de justice (2025)
IN DUBIO PRO REO;LÉSION CORPORELLE SIMPLE;VOIES DE FAIT;MENACE(DROIT PÉNAL);INDEMNITÉ(EN GÉNÉRAL);ASSISTANCE JUDICIAIRE | CPP.10.al3; CP.123.al1; CP.126; CP.180; CPP.429; CPP.136